Professional burnout among teachers in the regular schools and youth villages in Israel - Azulay, Vered (Rocznik Pedagogiczny, 2019)
The research study addresses the burnout of teachers who teach in regular schools vs. burnout among teachers who teach in youth villages in Israel. The research participants consist of 73 teachers who work with at-risk youths in youth villages in Israel and 70 teachers who work in regular schools, making a total of 143 teachers. A 5-segment self-reporting questionnaire was distributed. The study found a difference in how teachers refer to the factors influencing their departure. In the youth villages, as the factors of support are greater, the factors of departure are more significant. Hence, it is possible to understand that the conclusion that arises from the study is that in order to prevent teacher burnout it is necessary to create many more sources of support, both in regular schools and in youth villages.